Exploring Opportunities in Using Digital Platforms for English Language Learning among Vocational Students in Pekanbaru - Gultom, Agustin Leoningrum; Herlinawati, Herlinawati; Herdi, Herdi; Hamuddin, Budianto (EDUTREND: Journal of Emerging Issues and Trends in Education, 2025)
This study investigates vocational students’ perceptions of the opportunities offered by digital platforms in English language learning. The research responds to the increasing role of educational technology in the post-pandemic era and the need to evaluate its pedagogical impact on vocational education contexts. A quantitative descriptive design was employed, involving 61 students from the Broadcasting and Culinary programs at SMK Negeri 3 Pekanbaru, Indonesia. Data were collected through a 21-item Likert-scale questionnaire (Cronbach’s α = 0.825). The results show that students hold a moderately positive perception of the opportunities provided by digital platforms (M = 3.27, SD = 0.684). The highest mean scores were recorded in listening (M = 3.49), grammar (M = 3.46), and writing (M = 3.39), indicating that digital tools effectively enhance these language competencies. The findings highlight the potential of digital platforms to support flexible, autonomous, and interactive English learning. However, their full potential is yet to be realized due to limited teacher facilitation and technological barriers. The study recommends strengthening digital pedagogy training for vocational teachers and integrating digital literacy into English curricula to optimize the benefits of technology in language education.